Evaluation of properties of rice straw particulate (RSP) filled poly (lactic acid) (PLA)/ thermoplastic tapioca starch (TPTS) blends biocomposites - Ku, See May (School of Biosystem Engineering, University Malaysia Perlis, 2016)
The ecological awareness has stimulated the use of the bio-based polymer instead of using synthetic or non-degradable polymer. Poly (lactic acid) (PLA), a biopolymer which can be synthesized from renewable resources has attracted much attention and interest as its biocompatibility, biodegradability, and recyclable nature. However, the poor properties of PLA such as high brittleness and poor thermal stability had stimulated the development of new material by several modifications. In this project, PLA was blended with thermoplastic tapioca starch (TPTS) and the physical, thermal, morphological, water resistance and mechanical properties of these biocomposites was determined. The effect of rice straw particulate (RSP) as filler to PLA/TPTS biocomposites on tensile properties, water resistance and morphological were investigated.